ROLE OF ENDOTHELIAL CELLS IN REGULATION OF APOPTOSIS OF HIV-1 INFECTED CD4+ LYMPHOCYTES - S. V. Boichuk (SPb RAACI, 2014)
Abstract. Vascular endothelial cells (VECs) are able to induce HIV1 replication in СD4+ Tcells, thus determining their resistance for apoptosis. The revealed facts are specific to EC/Tcell culture and are stipulated by the cellcell interactions between the VECs and HIV1 producing cells, thus being a consequence of activation of ‘productively infected’ T cells.